2009
DOI: 10.1038/nature08265
|View full text |Cite
|
Sign up to set email alerts
|

Co-translational mRNA decay in Saccharomyces cerevisiae

Abstract: The rates of RNA decay and transcription determine the steady state levels of all mRNAs and both can be subject to regulation. While the details of transcriptional regulation are becoming increasingly understood, the mechanism(s) controlling mRNA decay remain unclear. In yeast, a major pathway of mRNA decay begins with deadenylation followed by decapping and 5’-3’ exonuclease digestion. Importantly, it is hypothesized that ribosomes must be removed from mRNA before transcripts are destroyed. Contrary to this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
318
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(348 citation statements)
references
References 23 publications
27
318
0
3
Order By: Relevance
“…However, with the finding of cytoplasmic P bodies, which accumulate, e.g., factors of the general mRNA degradation pathway but no ribosomes, it was proposed that mRNA decapping could occur only in P bodies after dissociation of the mRNA from ribosomes (11,(37)(38)(39)(40)(41)(42). More recently, Coller and coworkers provided additional experimental evidence to support the initial hypothesis of cotranslational degradation of some mRNAs in yeast (43,44). In this study, we significantly extend the experimental support for the hypothesis that the ribosome is a very general site not only for general 5=-to-3= mRNA degradation in Drosophila but also for the miRNA-mediated mRNA degradation pathway.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, with the finding of cytoplasmic P bodies, which accumulate, e.g., factors of the general mRNA degradation pathway but no ribosomes, it was proposed that mRNA decapping could occur only in P bodies after dissociation of the mRNA from ribosomes (11,(37)(38)(39)(40)(41)(42). More recently, Coller and coworkers provided additional experimental evidence to support the initial hypothesis of cotranslational degradation of some mRNAs in yeast (43,44). In this study, we significantly extend the experimental support for the hypothesis that the ribosome is a very general site not only for general 5=-to-3= mRNA degradation in Drosophila but also for the miRNA-mediated mRNA degradation pathway.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, it was postulated that mRNA decapping would require the dissociation of the mRNA from the ribosome followed by their accumulation in P bodies (11,(37)(38)(39)(40)(41)(42). In contrast, more recently Hu et al (43,44) have shown decapped degradation intermediates of several mRNAs, vector with a 3ϫ Flag sequence downstream of the metallothionein promoter in the pMK33/pMTHy backbone, followed in frame by a gateway cassette (Life Technologies), was constructed. The E. coli BirA ligase was PCR amplified and recombined into the pDONR221 plasmid.…”
mentioning
confidence: 99%
“…The main axes of the ellipses reveal that the errors in the estimation of synthesis and decay rates are not independent, yet small enough to prove that the coupling is not due to estimation variance. Brengues et al 2005;Hu et al 2009). There is also evidence that nuclear and cytoplasmic mRNA metabolism are linked.…”
Section: Discussionmentioning
confidence: 99%
“…During transcription, the mRNA receives a 59-cap and a 39-poly(A) tail. The mature mRNA is then exported to the cytoplasm, translated, and eventually degraded cotranslationally (Hu et al 2009). Cytoplasmic mRNA degradation generally begins with shortening of the poly(A) tail by the Ccr4-Not complex, which contains the deadenylases Ccr4 and Pop2 (also known as Caf1) (Liu et al 1998;Tucker et al 2001).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…First, the initiation region is decapped to prevent the assembly of new ribosomes. Second, the ribosomes present on the mRNA at the moment of decapping are allowed to finish their translation [9,14]. While degradation of mRNA before completion of protein production looks like a wasteful process at first sight, it is also a control mechanism that enhances the efficiency of protein synthesis [15].…”
Section: Introductionmentioning
confidence: 99%